Not all that glitters is gold: Political stability and trade in Sub-Saharan Africa - Simplice Asongu; Thales P. Yapatake Kossele; Joseph Nnanna (African Governance and Development Institute (AGDI), 2021)
This study examines linkages between political stability and trade openness dynamics in a panel of 44 countries in SSA from 1996 to 2016. The empirical evidence is based on the generalized method of moments. From the findings, the negative relationship between political stability and merchandise trade is not significant while the negative relationship between political stability and trade openness (exports plus imports) is significant. Hence, the findings do not validate the tested hypothesis that political stability/no violence increases trade in the sub-region. The perspective that some forms of political stability can slow down and prevent international trade is consistent with Oslon in Rise and Decline of Nations (RADON) and recent contributions to the economic development literature which have shown that not all forms of political stability are development friendly because much depends on the extent to which stability translates into, inter alia, good governance. The principal policy implication is that standards of political governance need to be boosted in order to improve the anticipated effects of political stability on trade, especially in the light of the ambitious African Continental Free Trade Area (AfCFTA). Other policy implications are discussed.
Keywords: F52; K42; O17; O55; P16; 330; Political Stability; Trade; Sub-Saharan Africa